Biomass Pyrolysis Liquefaction Technique: State of Research and Development Trends. Issue 2 (August 2020) - Li, Jie; Li, Nan; Qiao, Yingyun; Zong, Peijie; Wang, Chengbiao; Tian, Yuanyu; Qin, Song
Abstract: Biomass as the only renewable carbon sources in nature are considered to be huge amount, environmentally friendly and carbon neutral resources. Exploiting biomass as an energy utilization not only maximizes deal with the agricultural and forestry waste, but also refining high value-added bio-based chemicals products. As one of the important means of bio-refinery conversion processes, biomass pyrolysis liquefaction technique (BPLT) has been popular in producing fuel product since the late 1970s due to its advantages in its short process, strong adaptability, rapid response, high conversion rate and easy commercialization, etc. This paper provides an overview of current research progresses in the BPLT. Summarizes the latest research results of the combined processes for BPLT in feedstock pretreatment, pyrolysis liquefaction process and bio-oil upgrading. In the section of feedstock pretreatment, three methods of microwave drying, baking and pickling are introduced. In the section of pyrolysis process, two new processes of catalytic pyrolysis and mixed pyrolysis are discussed. The final part of the paper deals with recent technologies from five aspects in the bio-oil upgrading: catalytic hydrogenation, catalytic cracking, catalytic esterification, emulsified fuel and separation and purification. Afterward, the paper analyzes the industrialization development trends of BPLT. The paper suggests that make the production and upgrading of pyrolysis oil to hydrocarbon fuels is an economically attractive path. By critically evaluating their potential and challenges, we finally conclude, with the continuous maturity of various technical links such as feed prep, fast pyrolysis and upgrading, BPLT is expected to form a relatively complete technology industrial chain within 5 to 8 years, and gradually realized the industrialization in the true sense.